MODEL KEMAUAN MEMBAYAR PAJAK BAGI WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA WAJIB PAJAK KANTOR PELAYANAN PAJAK PRATAMA SLEMAN) - Hadri Kusuma; Via Rizkiana (Islamic Economics and Business Faculty of UIN Antasari, 2012)
Studies on tax generally focus on factors related to willingness of tax payers to pay theirtaxes. The present research develops previous study models by adding two new variables. Thefirst one is perception on the taxing officers and the second one is criteria of complying taxpayers. This study also employs an underused theory, the theory of planned behavior. Based onthe data gathered from 150 respondents, this study confirms the theory. More specifically, theawareness of tax payers, good perception on the effectiveness of tax service system, and percep-tions on the criteria of complying tax payers positively influence the overall willingness to paytaxes. Meanwhile, perceptions on taxing officers and knowledge and understanding on tax regula-tions do not influence the willingness of personal tax payers to pay taxes.